Knowledge Transmission in Light of Recent Transformations in the Workplace - Cloutier, Esther; Ledoux, Élise; Fournier, Pierre-Sébastien (Relations industrielles / Industrial Relations, 2012)
In a context of changing demographics and transformations to the world of work, concerns about age management are gradually turning into concerns about knowledge management. The vast experiential knowledge and diverse skills developed by workers to cope with the numerous situations encountered in the course of their work and to protect themselves against risks to their health and safety constitute part of the intangible assets vital to the sustainability of worker expertise and even the survival of the organization. Management practices play an important role in helping safeguard experiential knowledge in organizations. However, the transformations that have been taking place in recent years in response to an unstable economic climate have driven organizations to introduce a number of changes in workplaces. Three case studies, conducted in Quebec, each focused on the study of a specific occupation (film technicians, food service helpers, and homecare nurses), and based on interviews and observations made in the field, will be presented in an effort to describe the impact of some of these changes, namely precarious employment, flexible management practices and work intensification, on knowledge sharing in real work situations. The results suggest that by undermining work teams and increasing the workload of experienced workers, these changes actually hinder the knowledge sharing process. In fact, in such a context, the work teams are continually being reconfigured, which can demotivate experienced workers who constantly have to initiate new recruits despite already having a work overload. Possible avenues for research are proposed with a view to helping organizations cope with these changes in a way that supports the experiential knowledge transfer and sharing process so vital to organizational performance and the preservation of worker health.